Acute Flaccid Myelitis: A Clinical Review - Murphy, Olwen C.; Pardo, Carlos A. (Seminars in Neurology, 2020)
Acute flaccid myelitis (AFM) is an emerging disorder primarily affecting children that is characterized by acute flaccid paralysis accompanied by abnormalities of the spinal cord gray matter on magnetic resonance imaging. In most cases, prodromal fever or respiratory symptoms occur, followed by acute-onset flaccid limb weakness. Respiratory, axial, bulbar, facial, and extraocular muscles may also be affected. The clinical manifestations have been described as “polio-like,” due to striking similarities to cases of poliomyelitis. The primary site of injury in AFM is the anterior horn cells of the spinal cord, resulting in a motor neuronopathy. Seasonal peaks of cases have occurred in the United States every 2 years since 2012. However, AFM remains a rare disease, which can make it challenging for physicians to recognize and differentiate from other causes of acute flaccid paralysis such as Guillain–Barre syndrome, spinal cord stroke, and transverse myelitis. Epidemiological evidence suggests that AFM is linked to a viral etiology, with nonpolio enteroviruses (in particular enterovirus D68) demonstrating a plausible association. The epidemiology, possible etiological factors, clinical features, differential diagnosis, treatment, and outcomes of AFM are discussed in this review.
Keywords: acute flaccid myelitis; acute flaccid paralysis; enterovirus D68; polio-like; poliomyelitis; transverse myelitis